Modeling Tacit and Explicit Knowledge Sharing to Enhance Marketing and Financial Performance of MSMEs in Indonesia - Andy Wijaya; Sisca Sisca; Setiyawami Setiyawami; Acai Sudirman (Journal of Management and Entrepreneurship Research, 2026)
Objective: This study investigates the key factors that encourage employees to participate in knowledge-sharing activities to improve the performance of micro, small, and medium enterprises (MSMEs) in Indonesia. Research Design & Methods: The research employed a quantitative explanatory design with a cross-sectional survey approach. Primary data were collected from 374 MSME owners in the food and beverage sector. The proposed research model and hypothesised relationships were analysed using partial least squares structural equation modelling (PLS-SEM). Findings: The results show that tacit and explicit knowledge sharing are influenced by different determinants and lead to different performance outcomes. Trust and employee attitudes strongly promote tacit knowledge sharing, which positively affects marketing performance. Conversely, explicit knowledge sharing is mainly shaped by trust and organisational structure and has a greater impact on financial performance. Overall, the findings illustrate various mechanisms through which knowledge-sharing practices enhance MSME performance. Implications & Recommendations: The study offers useful insights for policymakers in designing policies that support knowledge-sharing initiatives among MSMEs. These policies may help enterprises improve operational efficiency, reduce costs, and increase profitability. In addition, this research contributes to the knowledge management literature by proposing a model specifically suited to the Indonesian MSME context. Contribution & Value Added: By distinguishing between tacit and explicit knowledge sharing, this study extends existing research through an empirical model that demonstrates how different organisational and individual factors shape knowledge-sharing behaviour and generate varied performance outcomes, thereby reinforcing knowledge management theory in small business settings.